1991
DOI: 10.1093/brain/114.5.2095
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Impairment in Early, Untreated Parkinson's Disease and Its Relationship to Motor Disability

Abstract: Current knowledge of cognitive dysfunction in Parkinson's disease (PD) has largely been obtained from studies of chronically treated patients in whom effects of disease chronicity, treatment, depression and dementia are confounding factors. Studies of untreated patients have examined few cognitive domains and relationships between cognition, depression and motor disability have been incompletely explored. Accordingly, we studied 60 consecutive patients with newly diagnosed, untreated, idiopathic PD and 37 matc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
344
3
12

Year Published

1993
1993
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 590 publications
(387 citation statements)
references
References 0 publications
28
344
3
12
Order By: Relevance
“…While there is little correlation between motor disability and cognitive impairment in PD (Cooper et al 1991), cognitive deficits tend to be associated with concurrent depression. For example, Starkstein et al (1989), in a matched control study examining cognitive impairment in PD patients with and without depression, found that the depressed PD patients performed significantly worse than the non-depressed PD subjects on all aspects of neuropsychological function, but especially frontal tasks.…”
Section: Affective Motor and Cognitive Dysfunction In Parkinson's DImentioning
confidence: 95%
“…While there is little correlation between motor disability and cognitive impairment in PD (Cooper et al 1991), cognitive deficits tend to be associated with concurrent depression. For example, Starkstein et al (1989), in a matched control study examining cognitive impairment in PD patients with and without depression, found that the depressed PD patients performed significantly worse than the non-depressed PD subjects on all aspects of neuropsychological function, but especially frontal tasks.…”
Section: Affective Motor and Cognitive Dysfunction In Parkinson's DImentioning
confidence: 95%
“…Thus, these findings support the idea that reduced stride-to-stride variability on the treadmill and the increased stride-to-stride variability typically seen in PD seems likely to be a result of changes in locomotor rhythmicity. (Cooper, Sagar, Jordan, Harvey, & Sullivan, 1991;Elias & Treland, 1999;Hausdorff et al, 2006;Yogev et al, 2005) and the putative reliance of a steady gait on this cognitive domain, we hypothesized that MPH may improve gait and reduce fall risk in patients with PD. MPH has a long history as the drug of choice for improving attention in children with ADHD, however, its potential to modify motor function is less known.…”
Section: Rhythmic Auditory Stimulation (Ras) Improves Gait Rhythmicitmentioning
confidence: 99%
“…Among the cognitive deficits which may be detected in patients with Parkinson's disease, deficits of executive functions (planning, problem solving, set-shifting), mediated by disruption of neural circuits involving the frontal lobes and the basal ganglia, are the most common in both early disease phases and in patients with advanced Parkinson's disease Cooper et al, 1991;Robbins et al, 1994;Taylor et al, 1986;Cools et al, 2001;Green et al, 2002). (Boller et al, 1984;Hovestadt et al, 1987;Ransmayr et al, 1987), impairment on language tasks of verbal fluency (Matison et al, 1982;Cooper et al, 1991) and tasks of oral naming (Peran et al, 2003) may occur in individual Parkinsonian patients since early phases and become more frequent in advanced Parkinson's disease (Green et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…(Boller et al, 1984;Hovestadt et al, 1987;Ransmayr et al, 1987), impairment on language tasks of verbal fluency (Matison et al, 1982;Cooper et al, 1991) and tasks of oral naming (Peran et al, 2003) may occur in individual Parkinsonian patients since early phases and become more frequent in advanced Parkinson's disease (Green et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation